Binding energy shifts for nitrogen‐containing graphene‐based electrocatalysts – experiments and DFT calculations. (22nd January 2016) - Kabir, S.; Artyushkova, K.; Serov, A.; Kiefer, B.; Atanassov, P.
Abstract : A detailed analysis of the physiochemical nature, thermodynamic properties, and electrochemical characterization of N motifs present in self‐assembled nitrogen functionalized transition metal and nitrogen doped graphene pyrolyzed materials has been conducted in this study. First principle density‐functional‐theory calculations were performed to assess the thermochemistry of Fe–Nx and graphitic‐N defects and to predict N1s core‐level‐shifts. Combining this prediction with our X‐ray photoelectron spectroscopy and rotating ring disk electrode experiments, we find that graphitic‐N contributes significantly to hydrogen peroxide formation in oxygen reduction reactions, while materials containing nitrogen coordinated transition metal result in the complete reduction of oxygen to water. Lastly, we show how the synergy of experimental, electrochemical, and computational approaches can accelerate the accurate identification and characterization of nitrogen functionalized graphene moieties present in pyrolyzed electrocatalysts for fuel cells. Copyright © 2016 John Wiley & Sons, Ltd.